Design of inclined omni-directional reflector for sidewall-emission-free micro-scale light-emitting diodes. (October 2022) - Hu, Xinpei; Cai, Junhu; Liu, Yongzhen; Zhao, Mengyun; Chen, Enguo; Sun, Jie; Yan, Qun; Guo, Tailiang
Highlight: This paper proposes a complete design, simulation, and fabrication of ODR for high-efficiency and sidewall-emission-free µLED pixels with inclined sidewalls. The µLED laminated structure is established to analyze the sidewall emission with an optimal inclination angle by two-dimensional finite-difference time-domain method. The overall LEE of the inclined µLED pixel with ODR can be increased by 2.24 times and the sidewall emission is reduced by 99.6% compared with conventional vertical µLED pixels. An ODR sample is prepared by magnetron sputtering, and an overall high reflectance of ∼ 99% covering the full visible spectrum at different incident angles is obtained. The experimental results are highly consistent with the simulation, which provides important guiding significance for µLED displays. Abstract: Micro-scale light emitting diode (µLED) reduces the front self-luminous display area by orders of magnitude, which brings the increase of sidewall emission and the resulting crosstalk between adjacent sub-pixels of displays. Reflector coating on the µLED's sidewall is effective for the collection and utilization of side emission light. However, the existing multilayer periodic dielectric mirrors are undesirable for all angular reflection. In this paper, an omni-directional reflector (ODR) is designed for the µLED display pixel to effectively utilize light leakage from the sidewall emission and improve the total light extraction efficiency (LEE). The designed ODR is insensitive to the angular distribution of the incident light, and has the capability to reflect the light reaching the µLED's sidewall into the escape cone for front emission. By introducing the two-dimensional finite-difference time-domain method, the µLED laminated structure is established to analyze the sidewall emission with an optimal inclination angle. By introducing the ODR for the inclined µLED pixel, the overall LEE can be increased by 2.24 times and the sidewall emission is reduced by 99.6% compared with conventional vertical µLEDs. Simulation and experimental results are in good agreement. The proposed ODR is expected to achieve the increase of LEE and sidewall-emission-free µLED displays.